STRUCTURAL-STRATEGIC APPROACHES TO COUPLE AND FAMILY THERAPY STRUGULING WITH ABUSE AND DOMESTIC VIOLENCE - Toma, Sergiu; Captari, Victoria; Toma, Natalia (CEP USM, 2018)
The issue and the key concepts and strategies that can be successfully used when providing couple therapy as part of the systemic therapy interventions using the basic concepts of strategic and structural family therapy are treated in the article. The two models, structural family therapy (as developed by Salvador Minuchin) and strategic family therapy (as developed by Jay Haley), are presented together because of their common emphasis on systems and structure. Both approaches aim to realign family organization to produce change in the entire system, and both are focused on the hierarchical organization of the family. The key perspective of this article is to present the Cloe Madanes approach and preconditions, and possible directions of interventions with families that experience domestic violence.

În articol este abordată problema, conceptele-cheie și strategiile care pot fi utilizate cu succes în realizarea terapiei de cuplu ca parte componentă a intervențiilor terapiei sistemice utilizând conceptele de bază ale terapiei strategice și structurale. Cele două modele – terapia structurală de familie (dezvoltată de Salvador Minuchin) și terapia strategică de familie (dezvoltată de Jay Haley) – sunt prezentate împreună datorită faptului că ambele acordă atenție sistemelor și structurii. Ambele abordări tind să realinieze organizarea familiei pentru producerea schimbării în întregul sistem și ambele sunt focusate pe organizarea ierarhică a familiei. Perspectivele centrale ale acestui demers ştiinţific constau în prezentarea abordării dezvoltate de Cloe Madanes, precum și a precondițiilor și posibilelor direcții de intervenții în familiile care cunosc violența domestică.
ABORDĂRI ALE PSIHOTERAPIEI DE CUPLU ȘI FAMILIE ÎN SITUAȚIE DE VIOLENȚĂ DIN PERSPECTIVĂ STRUCTURALISTĂ ȘI STRATEGICĂ
Keywords: structural family therapy; strategic therapy; family violence; couple therapy; psychotherapy; coalitions; maladaptive transactions; accommodation; boundaries; structurală de familie; terapie strategică de familie; violență domestică; terapie de cuplu